Comprehensive study on elastic moduli prediction and correlation of glass and glass ceramic derived from waste rice husk - Chee, Sun Lee; Matori, Khamirul Amin; Ab Aziz, Sidek; Mohamed Kamari, Halimah; Ismail, Ismayadi; Mohd Zaid, Mohd Hafiz (Hindawi Publishing Corporation, 2017)
Zinc silicate (ZnO–SiO2) systems were fabricated using zinc oxide (ZnO) and white rice husk ash (WRHA) with compositions of (ZnO)x(WRHA)1−x (